2023
DOI: 10.48550/arxiv.2302.04247
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

X-Ray Detection of the Galaxy's Missing Baryons in the Circum-Galactic Medium of L$^*$ Galaxies

Abstract: The amount of baryons hosted in the disks of galaxies is lower than expected based on the mass of their dark-matter halos and the fraction of baryon-to-total matter in the universe, giving rise to the so called galaxy missing-baryon problem. The presence of cool circum-galactic matter gravitationally bound to its galaxy's halo up to distances of at least ten times the size of the galaxy's disk, mitigates the problem but is far from being sufficient for its solution. It has instead been suggested, that the gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Also, X-ray absorption entirely depends on metal ions, which makes results dependent on the assumed abundance ratios of metals and the metal-to-hydrogen ratio. In addition to that, the lack of sufficient X-ray-bright QSO sightlines passing through the CGM of external galaxies limits the scope to probe the hot CGM of external galaxies in absorption (e.g., Mathur et al 2021;Nicastro et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Also, X-ray absorption entirely depends on metal ions, which makes results dependent on the assumed abundance ratios of metals and the metal-to-hydrogen ratio. In addition to that, the lack of sufficient X-ray-bright QSO sightlines passing through the CGM of external galaxies limits the scope to probe the hot CGM of external galaxies in absorption (e.g., Mathur et al 2021;Nicastro et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The primary source of this information comes from absorption line spectroscopy, with surveys such as COS-Halos (Tumlinson et al 2013;Werk et al 2013Werk et al , 2016, the Keck Baryonic Structure Survey (Rudie et al 2012(Rudie et al , 2019Erb et al 2023), COS-Dwarfs (Bordoloi et al 2014), COS-GASS (Borthakur et al 2015(Borthakur et al , 2016, and the Cosmic Ultraviolet Baryon Survey (Chen et al 2020;Zahedy et al 2021;Qu et al 2022), using bright background quasars as light sources. Most of this work has been at rest-frame UV wavelengths, although some work has been done inX-ray wavelengths (e.g., Comparat et al 2022;Nicastro et al 2023). Observations such as these have shown that the CGM is highly ionized, extended, and multiphase, with warm ions such as C IV and Si IV being found at similar velocities as colder ions, such as Mg II, N II, and Si II (Tripp et al 2011;Meiring et al 2013;Burchett et al 2015Burchett et al , 2019.…”
Section: Introductionmentioning
confidence: 99%